(untitled) (Eurasian Research Bulletin, 2022)
Use of pedagogical new technologies in the modern educational process. The article deals with the issues of new pedagogical technologies in the modern educational process, which will help students to learn their quality in education, learn the material in the disciplines and in the future become good specialists in their field.